Z-score model of foetal ascending aorta diameter distensibility - Chen, Fuli; Zeng, Shi; Yi, Aijiao; Chen, Lihua; Zhou, Dan; Liu, Yushan; Yao, Longmei (Frontiers in Cardiovascular Medicine, 2022)
Objective: The purpose of this study is to establish Z-scores models of normal foetal ascending aorta diameter and diameter distensibility. Methods: The maximum systolic diameter (Dmax), minimum diastolic diameter (Dmin), and diameter distensibility of the sinotubular junction were measured and taken as dependent variables in 490 normal foetuses at 18-40 gestational weeks, while gestational age (GA), biparietal diameter (BPD), and femoral length (FL) were taken as independent variables. The data were subjected to regression analysis, and the best-fitting equations for the dependent variables based on the independent variables were determined. The fitting equations were then applied to construct the Z-scores models. Results: The Dmax, Dmin and diameter distensibility in normal foetuses between 18 and 40 weeks of GA could be evaluated utilising Z-scores models. Dmax and Dmin increased significantly with increasing GA, BPD and FL. Diameter distensibility, assessed as (Dmax - Dmin) / Dmin, decreased significantly with increasing GA, BPD, and FL. Conclusions: The Z-scores are valuable, and can be utilised as a potent supplement to the traditional approach as they can indirectly reflect the development of foetal ascending aortic elastic property.